Ketoacidosis as a presenting symptom of diabetes in a eighteen month old infant: a case report - Mohan, Amrita; A., Sunkad M.; B., Javali S.; Vernekar, Sowmya; Hidakal, Shilpa (International Journal of Contemporary Pediatrics, 2020)
There is a world-wide trend in rise of diabetes cases. There is also rise in the trend of any one person getting diabetes at an early age. However, diabetes is fairly less common in children less than 5 years. The manifestation of diabetes too can be peculiar in very young children. Then managed as per standard protocol, results can be rewarding. Ours is secondary healthcare facility with all diagnostic equipment and consultants available round the clock. Authors describe one case finding of diabetic ketoacidosis. The baby aged 18 months presented with cold, cough, fever and air hunger (breathing deeply), referred by family doctor. The prompt diagnosis, rehydration, insulin infusion helped in recovery. Complete blood tests confirmed the presence of random blood sugar 345mg%, pH 7.05, Ketone bodies present in urine. While there was Leukocytosis, tests for Dengue Fever and Typhoid were negative. Identification of ketoacidosis and prompt treatment can save children.